Delay in healthcare seeking, diagnosis, and treatment of patients with tuberculosis: A cross-sectional study - Mahendra Chouksey,; Arya, Vimal; Nilima Takhelchangbam, (Asian Journal of Medical Sciences, 2023)
Background: One of the greatest challenges in the fight against tuberculosis (TB) is the delay in seeking medical care among those who are sick. This can be complemented by delays in providing prompt health-care services. Aims and Objectives: The aims of this study were to estimate the number of patients facing delays and to understand the various reasons for individual and health system delays. Materials and Methods: In this cross-sectional study, new sputum positive cases of >18 years registered at the two TB Units of two community health centers of a district in Uttar Pradesh from March 2018 to April 2019 were included. The primary outcome was patient delay and health system delay. They were assessed from patient interviews as well as through records. Results: A total of 120 patients were included in the study of which, 76 had been subjected to one or the other form or a combination of delay. The factors such as age, education level, occupation, socioeconomic condition, and the walking duration to the nearest health center were found to be significantly associated with delay. The patient delay was seen in 37 (30.8%) with median delay of 45 days (interquartile range [IQR] 37–53). The health system delay was observed in 48 (40.0%) patients with median delay of 24.5 days (IQR 12.0–47.2). Conclusion: In spite of robust program implementation, patient factor delays continue to prevail which contributes to the total delay. Addressing delay in Tb is of utmost important so as to progress to TB elimination.